Demián : historia de la juventud de Emilio Sinclair - Hesse, Hermann 1877-1962 (Ediciones Cultura, 1914)
First major novel by Nobel Prize-winning author explores the fundamental duality of existence through the tale of a troubled young man's confusion about life's conflicting values. Recounted in engaging prose, this brilliant psychological portrait offers a poignant statement of the terrors and torments of adolescence.